2000
DOI: 10.1097/00000539-200012000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Cognition After Coronary Artery Surgery Is Not Related to Postoperative Jugular Bulb Oxyhemoglobin Desaturation

Abstract: During the early postoperative period after coronary artery bypass grafting (CABG) surgery, many patients experience jugular bulb oxyhemoglobin desaturation (SjO(2) < 50%). We sought to determine whether SjO(2) during cardiopulmonary bypass and the early postoperative period influenced long-term cognitive performance after CABG surgery. One hundred two patients completed a battery of cognitive tests the day before and 3 mo after CABG surgery. A General Cognitive Score was generated from these tests as an overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 30 publications
0
16
1
2
Order By: Relevance
“…All functional domains were affected; there was no selective impairment. Robson et al [10] found no relationship between intraoperative and post-operative episodes of desaturation and post-operative cognitive decline measured 3 months after surgery using a battery of 11 tests. In contrast, Yoshitani et al [11] found that high SjO 2 levels 10 min after start of surgery and at 30 8C during rewarming predicted cognitive decline 10 -14 days following cardiac surgery with hypothermic CPB using a brief mental status test and a test of visual memory.…”
Section: Discussionmentioning
confidence: 98%
“…All functional domains were affected; there was no selective impairment. Robson et al [10] found no relationship between intraoperative and post-operative episodes of desaturation and post-operative cognitive decline measured 3 months after surgery using a battery of 11 tests. In contrast, Yoshitani et al [11] found that high SjO 2 levels 10 min after start of surgery and at 30 8C during rewarming predicted cognitive decline 10 -14 days following cardiac surgery with hypothermic CPB using a brief mental status test and a test of visual memory.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, further studies are necessary to determine if amelioration of the SjvO 2 value is associated with postoperative neurological dysfunction. Robson et al 20 provided evidence that jugular bulb catheters were not very accurate during bypass, possibly due to increased vessel wall contact; however, in a previous study, 22 we assessed the accuracy of our oximetric catheter system and found an excellent correlation between oximetry catheter values for SjvO 2 and simultaneous SjvO 2 values obtained from samples of jugular venous blood measured in a CO-oximeter. In conclusion, we observed decreased SjvO 2 values in the early phase of CPB more often in normothermic CPB than in hypothermic CPB in elderly patients.…”
Section: Study Limitationsmentioning
confidence: 78%
“…We did not find any difference in the incidence of postoperative neurological dysfunction between our two groups, and it is unclear whether the SjvO 2 value was associated with the improvement of postoperative neurological dysfunction. 20 Robson et al 20 found average SjvO 2 values during hypothermic CPB, and in the early postoperative phase, but this was not associated with cognitive status 3 months after surgery performed under normothermic CPB. In contrast, Yoshitani et al 21 reported that a high SjvO 2 was associated with cognitive dysfunction after the operation.…”
Section: Study Limitationsmentioning
confidence: 98%
“…El nivel educacional e intelectual también fue similar entre los grupos. Entre las pruebas neurocognitivas basales, sólo la puntuación del test Aprendizaje Verbal Auditivo de Rey (RAVLT; evalúa memoria de fi jación y aprendizaje reciente, susceptibilidad a la interferencia, memoria a medio plazo y benefi cio del reconocimiento [38][39][40] ) fue diferente entre ambos grupos, siendo más alta en el grupo que presentó DCPO (P = 0,028, Mann-Whitney U-test, Tabla 2). Las características perioperatorias también fueron similares entre ambos grupos, al igual que los tiempos de extubación y de estancias hospitalaria y UCI (Tabla 3).…”
Section: Resultsunclassified
“…Evalúan la coordinación visuo-manual y fl exibilidad cognitiva, memoria declarativa [38][39][40] , inteligencia y lenguaje.…”
Section: Valoración Neurocognitivaunclassified